TGF-β and TNF-α interaction promotes the expression of MMP-9 through H3K36 dimethylation: implications in breast cancer metastasis - Kochumon, Shihab; Al-Sayyar, Amnah; Jacob, Texy; Bahman, Fatemah; Akhter, Nadeem; Wilson, Ajit; Sindhu, Sardar; Hannun, Yusuf A.; Ahmad, Rasheed; Al-Mulla, Fahd (Frontiers in Immunology, 2024)
Increased MMP-9 expression in the tumor microenvironment (TME) plays a crucial role in the extracellular matrix remodeling to facilitate cancer invasion and metastasis. However, the mechanism of MMP-9 upregulation in TME remains elusive. Since TGF-β and TNF-α levels are elevated in TE, we asked whether these two agents interacted to induce/augment MMP-9 expression. Using a wellestablished MDA-MB-231 breast cancer model, we found that the synergy between TGF-β and TNFα led to MMP-9 upregulation at the transcriptional and translational levels, compared to treatments with each agent alone. Our in vitro findings are corroborated by co-expression of elevated MMP-9 with TGF-β and TNF-α in human breast cancer tissues. Mechanistically, we found that the MMP-9 upregulation driven by TGF-β/TNF-α cooperativity was attenuated by selective inhibition of the TGF-βRI/Smad3 pathway. Comparable outcomes were observed upon inhibition of TGF-β-induced phosphorylation of Smad2/3 and p38. As expected, the cells defective in Smad2/3 or p38-mediated signaling did not exhibit this synergistic induction of MMP-9. Importantly, the inhibition of histone methylation but not acetylation dampened the synergistic MMP-9 expression. Histone modification profiling further identified the H3K36me2 as an epigenetic regulatory mark of this synergy. Moreover, TGF-β/TNF-α co-stimulation led to increased levels of the transcriptionally permissive dimethylation mark at H3K36 in the MMP-9 promoter. Comparable outcomes were noted in cells deficient in NSD2 histone methyltransferase. In conclusion, our findings support a cooperativity model in which TGF-β could amplify the TNF-α-mediated MMP-9 production via chromatin remodeling and facilitate breast cancer invasion and metastasis.